Evaluating pharmacological THRomboprophylaxis in Individuals undergoing superficial endoVEnous treatment across NHS and private clinics in the UK: a multi-centre, assessor-blind, randomised controlled trial—THRIVE trial - John Norrie; Rebecca Lawton; Joseph Shalhoub; Beverley J Hunt; Annya Stephens-Boal; Tamara Everington; Joanne Dunbar; Sarah Onida; Layla Bolton; Manjit Gohel; A H Davies; Laura Burgess; et al. (BMJ Open)
Introduction Endovenous therapy is the first choice management for symptomatic varicose veins in NICE guidelines, with 56–70 000 procedures performed annually in the UK. Venous thromboembolism (VTE), including deep vein thrombosis (DVT) and pulmonary embolism (PE), is a known complication of endovenous therapy, occurring at a rate of up to 3.4%. Despite 73% of UK practitioners administering pharmacological thromboprophylaxis to reduce VTE, no high-quality evidence supporting this practice exists. Pharmacological thromboprophylaxis may have clinical and cost benefit in preventing VTE; however, further evidence is needed. This study aims to establish whether when endovenous therapy is undertaken: a single dose or course of pharmacological thromboprophylaxis alters the risk of VTE; pharmacological thromboprophylaxis is associated with an increased rate of bleeding events; pharmacological prophylaxis is cost effective.Methods and analysis A multi-centre, assessor-blind, randomised controlled trial (RCT) will recruit 6660 participants from 40 NHS and private sites across the UK. Participants will be randomised to intervention (single dose or extended course of pharmacological thromboprophylaxis plus compression) or control (compression alone). Participants will undergo a lower limb venous duplex ultrasound scan at 21–28 days post-procedure to identify asymptomatic DVT. The duplex scan will be conducted locally by blinded assessors. Participants will be contacted remotely for follow-up at 7 days and 90 days post-procedure. The primary outcome is imaging-confirmed lower limb DVT with or without symptoms or PE with symptoms within 90 days of treatment. The main analysis will be according to the intention-to-treat principle and will compare the rates of VTE at 90 days, using a repeated measures analysis of variance, adjusting for any pre-specified strongly prognostic baseline covariates using a mixed effects logistic regression.Ethics and dissemination Ethical approval was granted by Brent Research Ethics Committee (22/LO/0261). Results will be disseminated in a peer-reviewed journal and presented at national and international conferences.Trial registration number ISRCTN18501431.